Transformation of Selected Fusarium Toxins and Their Masked Forms during Malting of Various Cultivars of Wheat - Edyta Ksieniewicz-Woźniak; Marcin Bryła; Dorota Michałowska; Agnieszka Waśkiewicz; Tomoya Yoshinari (Toxins, 2021)
This study investigated the impact of malting of six wheat cultivars inoculated with Fusarium culmorum on the dynamics of content changes of selected Fusarium toxins. The grains of all the tested cultivars showed a high content of deoxynivalenol (DON), zearalenone (ZEN), and their derivatives, whereas nivalenol (NIV) and its glucoside were found only in the Legenda cultivar. Our experiments confirmed that the malting process of wheat grain enables the secondary growth of Fusarium, and mycotoxin biosynthesis. The levels of toxins in malt were few-fold higher than those in grain; an especially high increase was noted in the case of ZEN and its sulfate as the optimal temperature and pH conditions for the biosynthesis of these toxins by the pathogen are similar to those used in the grain malting process. This is the first paper reporting that during the malting process, biosynthesis of ZEN sulfate occurs, instead of glycosylation, which is a typical modification of mycotoxins by plant detoxication enzymes.